On the Mission of Humanitarian Education in Higher Technical School - A. A. Polonnikov (Высшее образование в России)
The paper follows into the critical pedagogy tradition. It analyzes discourses of renewing the sense of teaching liberal disciplines, philosophical ones in the first place, in higher school, with factors of lowering their status identified in it. Among those factors are as follows: giving up the acknowledgement of liberal education crisis, disciplinary isolation, prevalence of scholarly activity model in academic subjects design, and subordination to “knowledge acquisition” process in the organization of educational practice. Education’s processual organization is opposed by an event one, in which a liberal knowledge status is determined in terms of “otherness”. The article considers a student’s gaining experience with otherness as a new mission of liberal disciplines in higher education, whereas this kind of experience is treated as an attempt to build a new educational universalism.